2018
DOI: 10.1111/liv.13983
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nonalcoholic steatohepatitis and significant fibrosis in non‐obese nonalcoholic fatty liver disease

Abstract: Aims We compared (a) demographic and clinical characteristics and (b) determinants of nonalcoholic steatohepatitis and significant fibrosis in non‐obese and obese nonalcoholic fatty liver disease. Methods A cross‐sectional study of 664 Asian subjects (mean age 53.1 years; men 50.3%) with biopsy‐proven nonalcoholic fatty liver disease and controls was conducted. Subjects were divided by their body mass index into obese (body mass index ≥25 kg/m2) and non‐obese (body mass index <25 kg/m2). Results Observations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…Although obesity has been considered as the main pathophysiological factor leading to metabolic syndrome, including NAFLD, non-obese individuals may also develop NAFLD. 32 Skeletal muscle is the primary target organ of insulin-mediated glucose disposal, and therefore, sarcopenia itself, independent of obesity, may aggravate IR. 33 In the current study, the significant association between LMS and Fibrosis FIB4 lost its statistical significance after adjustment for IR, implicating that IR plays an important role in the relationship between LMS and advanced fibrosis in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity has been considered as the main pathophysiological factor leading to metabolic syndrome, including NAFLD, non-obese individuals may also develop NAFLD. 32 Skeletal muscle is the primary target organ of insulin-mediated glucose disposal, and therefore, sarcopenia itself, independent of obesity, may aggravate IR. 33 In the current study, the significant association between LMS and Fibrosis FIB4 lost its statistical significance after adjustment for IR, implicating that IR plays an important role in the relationship between LMS and advanced fibrosis in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Many research have shown that HFD-induced lipid metabolism disorder could lead to metabolic disorder, which is an important factor of hyperlipidemia and obesity (Kim et al, 2018;Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Such speculation is supported by a recent study with 664 biopsy-proven NAFLD Asian patients showing that the severity of hepatic histology in nonobese NAFLD is comparable to that in obese NAFLD. [33] Consistently, a study of 466 Caucasian subjects with biopsy-proven NAFLD demonstrated that lean NAFLD is characterized by a severe histological picture similar to that of obese NAFLD and the former cases are more progressed compared to overweight cases. [34] In our study, we attempted to evaluate the association between lean NAFLD severity and future diabetes risk.…”
Section: Discussionmentioning
confidence: 85%